Productivity Growth in Mexico : Understanding Main Dynamics and Key Drivers - Iacovone, Leonardo; Munoz Moreno, Rafael; Olaberria, Eduardo; Pereira Lopez, Mariana De La Paz (World Bank, Washington, DC, 2022)
The report undertakes, for the first time, a comprehensive firm-level analysis of the entire Mexican economy over 25 years, relying on the last six rounds of the Economic Census, which were conducted between 1994 and 2019 and surveyed more than 20 million businesses. It finds that Mexico’s disappointing aggregate productivity masks large differences in productivity levels and growth across locations, sectors, and firms. A geographic productivity divide runs between the North-Center and South of Mexico, but large differences also persist between municipalities within regions. Fast-growing municipalities that have caught up to the Mexican productivity frontier, including in the South, while others have failed to grow at all. There is also a divide between modern firms, with access to finance and strong management, integrated into global value chains (GVCs), and more traditional firms characterized by limited access to finance and weak capabilities, unable to benefit from Mexico’s regional and global integration. The report shows that Mexico’s aggregate productivity is weakened by structural factors at industry and firm level — access to finance, lack of incentives to invest in technology, managerial capacities, and the business environment — that impede productive firms’ access to resources. The rest of this summary gives a synopsis of the report’s main findings and recommendations.